Surgical extraction of a supernumerary tooth in a patient with Angelman syndrome - case report - Małgorzata Lipczyńska-Lewandowska; Damian Chybicki; Gaja Torbicka; Michał Ceranka; Anna Janas-Naze (Kazimierz Wielki University, 2020)
The article discusses the problem of dental-occlusal disorders in patients with rare Angelman syndrome, based on the case report of an 8-year-old patient.